STRIKE-SLIP FAULT IDENTIFICATION BENEATH OF THE WIRIAGAR OIL FIELD - Accep handyarso; H.M. Saleh H.M. Saleh (Scientific Contributions Oil and Gas, 2017)
The oil and gas explorations in the Eastern Indonesia is still lagging behind the Western Indonesia. The complexity of the geological structures and the geographical conditions caused Eastern Indonesia become virgin areas which commonly known as the frontier areas, such that the cost and risks of the oil and gas explorations become higher. Wiriagar Field is the only oil production fi eld in the Bintuni Basin with signifi cant production capacity. The search for new oil and gas location can use the analogy of the existing oil and gas fi elds. Thus the pattern of subsurface geological structures beneath the Wiriagar Field can be used as a template (key) in the search for new oil and gas fi eld in the Bintuni Basin. Analysis of the subsurface geological structures in the Wiriagar area conducted based on the gravity data with seismic and exploration well data as the constraints. There is an indication of the left-lateral strike-slip fault existence with SW-NE direction intersecting the anticline ridge with NW-SE alignment. The strike-slip fault then verifi ed through seismic section data. This structure pattern is suspected to infl uence the trap of the hydrocarbon which allows the migration from PreKais Formation to the Reservoir of Kais Formation beneath the Wiriagar Oil Field.